Activity of erythrocyte antioxidant enzymes in healthy women depends on age, BMI, physical activity, and diet - Elżbieta Cecerska-Heryć; Klaudia Krauze; Angelika Szczęśniak; Aleksandra Goryniak-Mikołajczyk; Natalia Serwin; Daria Śleboda-Taront; Roksana Jacek; Rafał Heryć; Anna Michalczyk; Barbara Dołęgowska (BMC, 2022)
Abstract Introduction Antioxidant enzymes protect the human body against the harmful effects of oxidative stress. The activity of antioxidant enzymes changes with age and depends on dietary nutrients such as fats and vitamins, which can have a significant impact on minimizing or exacerbating oxidative stress. Aim To examine the effect of age, BMI, diet, physical activity, and smoking status on the activity of erythrocyte antioxidant enzymes catalase, glutathione reductase, glutathione peroxidase glutathione S-transferase, superoxide dismutase, and glutathione concentrations in healthy women. Material and methods This study included 98 healthy women aged between 20 and 65 years. All women underwent anthropometric tests: body weight, height, hip, and waist circumference. Antioxidant activity in erythrocytes was measured by spectrophotometric methods. Results Catalase activity increased significantly with age (p < 0.001), while superoxide dismutase activities and glutathione decreased with age (p = 0.008, p = 0.023, respectively). Women with a lower BMI (emaciation) had higher superoxide dismutase activity than those in the first degree of obesity (p = 0.009). Conclusions (1) Increased catalase activity with age may signify a large amount of hydrogen peroxide resulting from malfunctioning antioxidant systems in old age. (2) A decline in superoxide dismutase activity with age may indicate inactivation of this enzyme, inappropriate SOD function in the presence of excessive amounts of hydrogen peroxide, and glycation of superoxide dismutase molecules. (3) A negative correlation between superoxide dismutase activity and the BMI index may indicate a decreased enzymatic activity in obese people.